Nonalcoholic fatty liver disease in patients with type 2 diabetes: a review article - Miranda Manrique, Gonzalo (2023)
Nonalcoholic fatty liver disease (NAFLD) is caused by a build-up of triglyceride macrovesicles in the liver not related toother etiologies such as alcoholism, medications or genetic disorders. The spectrum of this condition includes nonalcoholic steatohepatitis (NASH) and simple fatty liver.In 2020, an international panel of experts proposed a new name for this entity and considered that the term “metabolicassociated fatty liver disease” (MAFLD) would be the most appropriate to refer to a comprehensive but simple set ofcriteria for the diagnosis of MAFLD, which is not related to the amount of alcohol consumption and can occur in patientsin any clinical setting.NAFLD is a manifestation of metabolic syndrome and shows high prevalence and risk of rapid progression in patientswith type 2 diabetes (T2DM). The current model considers that this process occurs as a consequence of “multiple hits” that could precede the fatty liver disease, this being the most appropriate explanation for the evolution of NAFLD in aninflammatory state. T2DM worsens NAFLD, leading to hyperglycemia and thus building a vicious circle.As for patients with diabetes, the risk of fibrosis must be assessed due to its impact on increased cardiovascular risk andprogression of liver disease. This task may be accomplished through non-invasive tests such as hepatic fibrosis biomarkers